Protocol for the preparation of zebrafish whole heart cell suspension for single-cell analyses - Karim Abu Nahia; Cecilia Lanny Winata (STAR Protocols)
Summary: Obtaining viable cell suspension that accurately represents the diversity of complex tissues is challenging due to the distinct characteristics of each cell type. Here, we present a protocol for preparing a single-cell suspension of the zebrafish embryonic whole heart, detailing steps for heart extraction, cell dissociation, quantification, and quality assessment. This suspension is compatible with downstream analysis on various single-cell platforms.For details on the use and execution of this protocol, please refer to Abu Nahia et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.